Population Genomics of Variegated Toad-Headed Lizard Phrynocephalus versicolor and Its Adaptation to the Colorful Sand of the Gobi Desert. (9th June 2022) - Jin, Yuanting; Aguilar-Gómez, Diana; Y C Brandt, Débora; Square, Tyler A; Li, Jiasheng; Liu, Zhengxia; Wang, Tao; Sudmant, Peter H; Miller, Craig T; Nielsen, Rasmus
Abstract: The variegated toad-headed agama, Phrynocephalus versicolor, lives in the arid landscape of the Chinese Gobi Desert. We analyzed populations from three different locations which vary in substrate color and altitude: Heishankou (HSK), Guazhou County (GZ), and Ejin Banner (EJN). The substrate color is either light-yellow (GZ-y), yellow (EJN-y), or black (HSK-b); the corresponding lizard population colors largely match their substrate in the degree of melanism. We assembled the P. versicolor genome and sequenced over 90 individuals from the three different populations. Genetic divergence between populations corresponds to their geographic distribution. We inferred the genetic relationships among these populations and used selection scans and differential expression to identify genes that show signatures of selection. Slc2a11 and akap12, among other genes, are highly differentiated and may be responsible for pigment adaptation to substrate color in P. versicolor .